Retrospective morphometric study of the suitability of renal arteries for renal denervation according to the Symplicity HTN2 trial criteria. Issue 1 (4th January 2016) - Schönherr, Elisabeth; Rehwald, Rafael; Nasseri, Parinaz; Luger, Anna K; Grams, Astrid E; Kerschbaum, Julia; Rehder, Peter; Petersen, Johannes; Glodny, Bernhard
Abstract : Objective: The aim of this study was to describe the renal arteries of humans in vivo, as precisely as possible, and to formulate an expected value for the exclusion of renal denervation due to the anatomical situation based on the criteria of the Symplicity HTN trials. Design and setting: In a retrospective cohort study, the renal arteries of 126 patients (57 women, 69 men, mean age 60±17.2 years (CI 57.7 to 63.6)) were segmented semiautomatically from high-contrast CT angiographies. Results: Among the 300 renal arteries, there were three arteries with fibromuscular dysplasia and one with ostial renal artery stenosis. The first left renal artery was shorter than the right (34±11.4 mm (CI 32 to 36) vs 45.9±15 mm (CI 43.2 to 48.6); p<0.0001), but had a slightly larger diameter (5.2±1.4 mm (CI 4.9 to 5.4) vs 4.9±1.2 mm (CI 4.6 to 5.1); p>0.05). The first left renal arteries were 1.1±0.4 mm (CI 0.9 to 1.3), and the first right renal arteries were 0.3±0.6 mm (CI 0.1 to 0.5) thinner in women than in men (p<0.05). Ostial funnels were up to 14 mm long. The cross-sections were elliptical, more pronounced on the right side (p<0.05). In 23 cases (18.3%), the main artery was shorter than 2 cm; in 43 cases (34.1%), the diameter was not >4 mm. Some 46% of the patients, or 58.7% when variants and diseases were taken into consideration, were theoretically not suitable for denervation. Conclusions: Based on these precise measurements, the anatomical situation as a reason for ruling out denervation appears to be significantly more common than previously suspected. Since this can be the cause of the failure of treatment in some cases, further development of catheters or direct percutaneous approaches may improve success rates.